ANT 2015/16: AWI airborne Radio-Echo Sounding data western DML over the Maud Belt and Ekström Ice Shelf (GEA-V-FMA project) - Eagles, Graeme; Ruppel, Antonia; Läufer, Andreas; Steinhage, Daniel; Helm, Veit (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system (Nixdorf et al., 1999) during the Arctic season of 2015. The profiles extend western DML over the Maud Belt and Ekström Ice Shelf to investigate the geodynamic evolution of East Antarctica, the Forster magnetic anomaly (GEA-V-FMA). The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.
Keywords: AWI EMR; DML; Dronning Maud Land; Ekström Isen; Maud Belt; Polar 5; radio-echo sounding